PEMDAS
parenthasees
exponents
multipilcarion
bla bla bla
that is important to know the differnece between
2x^2 and (2x)^2
2x^2=2*x*x
(2x)^2=2*2*x*x
so
(-3b)^4=-12b^4
pemdase so look at both sides
left side
negative to an even power means result is positive
right side
-12 times b^4
the -12 is not influcnced because that is multiply and exponents come first so it will remain negative
(+)=(-)
false
you could also evaluate it
(-3b)^4=-3b*-3b*-3b*-3b=81b^4
-12b^4=-12b^4
81b^4=-12b^4
divide b^4
81=-12
false
no